Angiostrongyliasis detected by next-generation sequencing in a ELISA-negative eosinophilic meningitis: A case report. (August 2020) - Zou, Yueli; Guan, Hongzhi; Wu, Honglong; Bu, Hui; Yan, Litian; Zhu, Yifei; He, Junying
Highlights: This case reported enzyme-linked immunosorbent assay (ELISA)-negative next-generation sequencing (NGS)-positive cerebral Angiostrongylus cantonensis . Angiostrongylus cantonensis was detected by NGS of the cerebrospinal fluid. NGS is a tool for etiological diagnosis. Abstract: Next-generation sequencing (NGS) is an emerging method with the potential of pan-pathogen screening. This study described a case of eosinophilic meningitis (EoM) with enzyme-linked immunosorbent assay (ELISA)-negative results for Angiostrongylus cantonensis ( A. cantonensis ), Trichinella spiralis and Paragonimus westermani and a positive identification of A. cantonensis by NGS in the cerebrospinal fluid .